Belleville Barbados, B. W. I. - (:unkn) unknown (The Main Library, University of the West Indies, Cave Hill Campus, Barbados is responsible for making this digital resource available., 2024)
An image of a postman and a woman standing on a residential street in Belleville, Barbados, W.I. Residential homes are visible to the right of the picture. The street is lined with palm trees. This is a divided back postcard. Back of the postcard A08 £8 (Handwritten in pencil). Published by Knights Ltd.
Landscape; Black & white; 3 ½” x 5 ½”
Keywords: Residential streets; Postal service; Women; Houses; Dwellings